Developing EFL teachers’ competence in designing learning materials through electronic English book design training - Usman Usman; Zulfah Fakhruddin; Hardiyanti Hardiyanti; Zam-Zam Adam; Kadaruddin Kadaruddin; Bita Rahmani (JINoP (Jurnal Inovasi Pembelajaran), 2023)
This study aims to develop the competence of teachers in designing English learning materials through electronic English book design training. This study was action research. The training was given to 7 English teachers at the Madrasah Tsanawiyah level (Islamic junior high school) with more than 5 years of teaching experience and proficiency in using computers. Data were collected by using product assessment, observation, and interviews. The data was analyzed by using descriptive qualitative analysis. The results show that teachers can create electronic books for English learning after receiving learning technology training with training materials including: (1) designing materials through PowerPoint, (2) changing materials in electronic form through I-spring, and (3) making electronic books with the android extension via APK builder. Indicators of the teacher’s competence in designing electronic books include: (1) being able to independently design the content in terms of explanation materials in the form of images, audio, and video and exercises in the form of quizzes equipped with assessments and (2) being able to independently design the appearance or layout of an electronic book consisting of cover, layout, and buttons.